A Primase-Induced Conformational Switch Controls the Stability of the Bacterial Replisome - Monachino, Enrico; Jergic, Slobodan; Lewis, Jacob S.; Xu, Zhi-Qiang; Lo, Allen T.Y.; O’Shea, Valerie L.; Berger, James M.; Dixon, Nicholas E.; van Oijen, Antoine M. (Molecular cell, 2020)
Recent studies of bacterial DNA replication have led to a picture of the replisome as an entity that freely exchanges DNA polymerases and displays intermittent coupling between the helicase and polymerase(s). Challenging the textbook model of the polymerase holoenzyme acting as a stable complex coordinating the replisome, these observations suggest a role of the helicase as the central organizing hub. We show here that the molecular origin of this newly found plasticity lies in the 500-fold increase in strength of the interaction between the polymerase holoenzyme and the replicative helicase upon association of the primase with the replisome. By combining in vitro ensemble-averaged and single-molecule assays, we demonstrate that this conformational switch operates during replication and promotes recruitment of multiple holoenzymes at the fork. Our observations provide a molecular mechanism for polymerase exchange and offer a revised model for the replication reaction that emphasizes its stochasticity. [Display omitted] There are at least two functional modes of interaction of Pol III and DnaB on DNAThe interaction between the CLC and DnaB strengthens ∼500-fold upon DnaG bindingA single copy of the τ subunit in the CLC is responsible for binding DnaBMultiple Pol IIIs can be at the fork, subject to the status of DnaB-DnaG interaction Monachino et al. show that dynamic interaction of the Escherichia coli DnaG primase and DnaB helicase affects the stability of the replisome and the cycling of DNA polymerase III complexes at the replication fork through a conformational switch in DnaB that toggles its affinity for the polymerase.